Frontline leadership in a distal employment relationship: a qualitative psychological contract perspective - Irai P; Arrowsmith J; Junaid F (Taylor and Francis Group on behalf of the Association of Industrial Relations Academics in Australia and New Zealand (AIRAANZ), 2025)
Frontline leadership is crucial to framing the psychological contract (PC), which governs implicit expectations and obligations between workers and their employers. Much of PC research focuses on white-collar and professional occupations, including in managing recent shifts between workplace and home-based working, and the dynamics of distal relationships in jobs such as driving are much less explored. This study explores the employment relationship, and in particular the supervisory role, in bus driving through the PC’s lens. Given the inherently subjective and relational nature of the PC and the dynamic context of Covid and industrial disputes in which the research was conducted, a qualitative approach was employed to understand how distal employment relationships influence the formation and fulfilment of PC. The findings highlighted structural challenges relating to privatisation and driver shortages, though it also underscored five distinct and relevant aspects of workplace support: trust, psychological safety, supervisor-bus driver exchange, co-worker relationships and relational leadership. Notably, drivers perceived under-delivery in these attributes were linked to inadequate perceived organisational support (POS) and PC breaches. These insights have implications for the broader literature on frontline leadership, POS, and PC while offering practical suggestions for improving employee relations and human resource management (HRM) in the industry.
Keywords: Psychological contract; relational leadership; bus drivers; trust; co-worker support